BASIC VECTORS OF MANAGEMENT OF JOINT COOPERATIVE INSTITUTIONS OF HIGHER EDUCATION - Світлана Бебко (Bulletin of Sumy National Agrarian University, 2022)
The article highlights the issues of management of joint cooperative institutions of higher education, substantiates that the formation of cooperative institutions of higher education is an effective form of organization of economic activity in many national markets of educational services. It is proved that joint cooperative institutions of higher education are economic organizations created with the participation of institutions of different countries. Therefore, such institutions have all the attributes of economic organization, but with certain features. The article defines the goal, which consists in the development and scientific substantiation of theoretical and methodological foundations, methodological approaches and practical recommendations for the management of cooperation of higher education institutions for the development of global competitiveness. In accordance with the set goal, the following tasks were formulated and completed: theoretical principles of management of cooperation of higher education institutions in a global environment were investigated; the role and main forms of development of cooperative structures in conditions of global competitiveness are outlined; the economic essence of the cooperative management of higher education institutions in market conditions is substantiated. It is substantiated that the autonomy of higher education institutions in developed countries is a management tool that in the social environment, provides a continuous process of socialization of the individual, allows management to focus on purely educational and research tasks. It is determined that in recent years the mechanisms of knowledge production and transfer have changed dramatically, the amount of knowledge and professionally relevant information is growing rapidly. Unlike the higher education institutions of the past, modern institutions operate in a competitive market environment, trying to provide themselves with more income from the provision of more educational and other services. It is estimated and substantiated that alternatives for the development of higher education institutions will be based on balancing the stated goals, environmental challenges and available resources. Different higher education institutions focus on different results: some strive to be leaders in the number of students, others aim to gain research status, others maintain a positive reputation in a particular field of science and education, others focus on high profitability and so on. Accordingly, individual development vectors will be considered in each case. These scenarios will be more accurate if they take into account as many significant factors as possible.